증강현실기술을 적용한 유아용 동화책 제작에 대한 연구 - 김태은(Tae-Eun Kim) (디지털콘텐츠학회논문지, 2017)
증강현실을 이용해 동화책을 조금 더 실감나고 몰입도 있게, 재미있게 제작하는 것은 교육적인 면에서 큰 의미가 있다. 본 연구에서는 아이들에게 보편적으로 널리 알려진 동화 이야기를 증강현실 동영상 콘텐츠로 제작하면서, 제작 방법에 대한 경험을 공유하고, 나아가 증강현실 기술을 도서출판분야로의 적용을 좀 더 쉽게 접근하는 가이드북 역할을 하고자한다. 또한, 본 개발에서는 증강현실 제작에 사용한 3D 모델링 제작방법, Unity3D 엔진 사용방법, Vuforia 마커 제작 방법까지 증강현실 콘텐츠 제작 초보자들에게 증강현실 동화책 제작에 관한 원리와 방식을 동영상과 함께 제공하여 교육현장에서 바로 활용 가능하도록 가이드 하는 연구이다. Using augmented reality to make children 's books more realistic, engaging, and funny makes a great sense in terms of education. The purpose of this study is to share the experience of the production method with the story of the fairy tale which is widely known to the children as the augmented reality video contents and to act as a guide book to make the application of the augmented reality technology to the field of book publishing easier. I want to. Also, in this development, the principles and the method of making augmented reality storybooks are provided to beginners of the augmented reality contents production including the 3D modeling production method used for the augmented reality production, the method of using Unity3D engine, and the method of producing the vuforia marker, It is a study that guides you to use it immediately. KCI Citation Count: 17